The Effects Of Pixel Aggregation On The Radiometric Properties Of Landsat-8 Satellite Imagery - Razali, Muhammad Fahmi; Asmala, A.; Nurul Iman, S B; Mohd, Othman * (Publications International, 2014)
This study aims to evaluate the effects of pixel aggregation on the radiometric properties of Landsat-8 satellite imagery. Two images of north-western Peninsular Malaysia (i.e. clear day and cloudy day) were selected for the study. The aggregated average method was used due to its simplicity and practicality. Paired sample t-test and similarity matrix analysis were performed to assess and evaluate the effects of aggregation to Landsat-8 radiometric properties. The results show that the higher the aggregation scale the lower the similarity to the original pixel value for all bands. However, pixel aggregation does not significantly change the radiometric properties of all bands in both images except for the infrared bands in the clear image.